Escape rate for cod (Gadus morhua) from the codend during buffer towing - Brinkhof, Jesse; Herrmann, Bent; Larsen, Roger B.; Sistiaga, Manu Berrondo (ICES Journal of Marine Science, 2017)
This is a pre-copyedited, author-produced version of an article accepted for publication in ICES Journal of Marine Science following peer review. The version of record "Brinkhof, J., Herrmann, B., Larsen, R. B. L., Sistiaga, M. B. (2017). Escape rate for cod (Gadus morhua) from the codend during buffer towing. ICES Journal of Marine Science" is available online at: http://dx.doi.org/10.1093/icesjms/fsx200 . https://academic.oup.com/icesjms/advance-article/doi/10.1093/icesjms/fsx200/4582356?searchresult=1 The high abundances of Northeast Arctic cod (Gadus morhua) in the Barents Sea have led to the development of a new fishing tactic called buffer towing. On factory trawlers, the trawl is deployed immediately after taking the catch onboard, a tactic used to ensure a continuous supply of fish is being processed. If the desired amount of fish is caught before the catch from the previous haul has been fully processed, the trawl is lifted off the seabed and towed at a given depth at low speed. This is called buffer towing. Cod that escape from the codend when the trawl is shallower than the initial fishing depth are exposed to an increased likelihood of barotrauma-related injuries, increased disease susceptibility, and predation, which could be lethal, or affect growth and reproduction capability. Therefore, this study quantified the escape rate and size selectivity during buffer towing of cod. A new analytical method was applied that allows using the same trawl configuration as applied during commercial fishing and avoids potential bias in the assessment of buffer towing size selection. Our results demonstrated a significant size selection for cod during buffer towing where cod measuring up to at least 42 cm in length were proven to escape. In particular, at least 60% of cod measuring 20 cm were estimated to escape during buffer towing. For cod measuring 30 and 40 cm, at least 53 and 45% were estimated to escape during buffer towing, respectively.